Kajian Yuridis Perlindungan Data Pribadi Pada Platform Media Sosial Studi Kasus Polresta Cirebon - Azahra, Nayla Alifah Azahra; Hafizd, Jefik Zulfikar; Muamar, Afif (Jurnal Hukum Ekualitas, 2025)
Social media platforms are used as databases of information including widely used personal data. Therefore, personal data protection is a crucial topic. This study aims to examine in more depth the legal protection of personal data on social media platforms and forms of misuse of personal data on social media in political dynamics in Cirebon Regency based on the ITE Law and the handling of misuse of personal data on social media platforms at the Cirebon Regency Police based on the ITE Law. The method used in this study is qualitative by utilizing a normative legal approach. Data collection techniques are literature studies and documentary studies. The results of the study show that legal protection of personal data in Indonesia is regulated in Law Number 19 of 2016 concerning Information and Electronic Transactions, especially in Article 26. In Cirebon Regency, the form of misuse of personal data that is widely reported by the public is cellphone numbers. In addition to cellphone numbers, there are also other forms, such as online loan practices (pinjol) and sniffing. Handling at the Cirebon Police regarding misuse of personal data on social media by conducting investigations and inquiries.